Fio a fio : a qualidade de vida de cuidadoras familiares de pacientes em hemodiálise após intervenção de oficinas de crochê - Chagas, Kaíza Oliva Donadia (2024)
Manual making and the production of pieces with one's own hands are reported in the literature as a way of expressing feelings, emotions and as an aid in coping with stressful events and situations. Handicraft practices with threads, such as crochet and knitting have been studied with a view of being tools that promote a feeling of well-being, development of creativity and autonomy. Usually, when approaching the process of caring for an ill family member, it is noted that the quality of life of family caregivers are influenced by treatment and illness: family caregivers often give up on their projects and struggle reconciling this role with formal employment relationships, in addition to routine care. For family caregivers of patients in hemodialysis, there is a great demand for caregiver availability due to the possibility of complications on treatment days. In this study, we applied three instruments to investigate the quality of life of seven family caregivers of hemodialysis patients at a hospital in Grande Vitória/ES: a semi-structured interview script, crochet workshops and the WHOQOL-Bref questionnaire (applied before and after the workshops). In the results we found the ambivalences of care: impotence, tiredness, exhaustion, but also love, gratitude and compassion when caring for family members. The crochet workshops were able to provide the presence of self, affection, fulfillment and well-being for caregivers, which helped to improve the perception of their quality of life